Korelasi Untuk Mengetahui Prestasi Siswa Terhadap Sosial Ekonomi Keluarga, Kegiatan Siswa Diluar Lingkungan Sekolah Dan Tingkat Motivasi Belajar Siswa Menggunakan Metode Apriori (Studi Kasus : SMP Negeri 2 Binjai) - Dina Ervianna Simarmata; Yani Maulita; Suria Alamsyah Putra (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Learning achievement is every learning activity carried out by students which will result in a change in themselves. The learning outcomes obtained by students are measured based on differences in behavior before and after learning is carried out. The economic conditions of students' families at SMP Negeri 2 Binjai have a significant influence on student learning achievement. Many students who come from families with economically disadvantaged backgrounds face various challenges that hinder the learning process. Financial limitations often mean they do not have adequate access to educational resources, such as books, the internet, and additional tutoring which can help improve understanding of subject matter. This research uses the Apriori method as a problem solving method, namely to correlate between Family Socio-Economics, Activities Students Outside the School Environment and Level of Student Learning Motivation with Student Achievement in class. If data A, G, K → O with Support 30% and Confident 100% and S*C value 30%. So, if a student from a family with an income of less than Rp. 1,000,000 who take part in extracurricular activities outside of school, and have family-driven motivation, will have academic achievement with good report cards. This research indicates that family socio-economic conditions have a significant impact on student academic achievement. Through data analysis, it can be seen that factors such as family income, student activities outside the school environment and the level of student motivation to learn can influence the extent to which students can achieve higher academic achievement.